Strategi Promosi Penerimaan Siswa Baru Di Raudhatul Athfal Perwanida 3 Palembang - Yuliana Yuliana; Edi Harapan; Achmand Wahidy (El-Idare, 2022)
This study aims to determine the promotion strategy of new student admissions at Raudhatul Athfal Perwanida 3 Palembang. The type of research used is field research (filed research) using a case study method approach (case study) which is descriptive qualitative with data collection techniques namely interviews, observation, and documentation. For data analysis techniques with the stages of data reduction, data presentation, and drawing conclusions. The results of the research are first, the promotion strategy used is a strategy to win the competition, a tactical strategy, and a value strategy. Second, the supporting factors in the implementation of the promotion strategy are having a clear segment, a fairly good brand, the trust of the public and alumni is still relatively high, and the advancement of information technology. Meanwhile, the inhibiting factors are that information technology facilities are still minimal, there are no special human resources for managing technology-based promotional media, and a small promotional budget. Third, there is no involvement of the foundation in thinking and determining the direction of development, the foundation's low attention to students who excel, and minimal providing information technology facilities provided by the foundation.